2017
DOI: 10.1038/srep40248
|View full text |Cite
|
Sign up to set email alerts
|

A fibrolytic potential in the human ileum mucosal microbiota revealed by functional metagenomic

Abstract: The digestion of dietary fibers is a major function of the human intestinal microbiota. So far this function has been attributed to the microorganisms inhabiting the colon, and many studies have focused on this distal part of the gastrointestinal tract using easily accessible fecal material. However, microbial fermentations, supported by the presence of short-chain fatty acids, are suspected to occur in the upper small intestine, particularly in the ileum. Using a fosmid library from the human ileal mucosa, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 64 publications
1
35
0
1
Order By: Relevance
“…The ability of the microbiota to utilize the seaweed fiber components as an energy source is primarily dictated by the presence of enzymes which can hydrolyze the various glycosidic bonds throughout the fiber structure [43]. There are numerous in vitro human fecal batch culture experiments previously carried out on each individual seaweed fiber (alginate/laminarin/fucoidan), and these studies have demonstrated that both alginate and laminarin fibers can be efficiently fermented by the human microbiota [24, 25, 31-35, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the microbiota to utilize the seaweed fiber components as an energy source is primarily dictated by the presence of enzymes which can hydrolyze the various glycosidic bonds throughout the fiber structure [43]. There are numerous in vitro human fecal batch culture experiments previously carried out on each individual seaweed fiber (alginate/laminarin/fucoidan), and these studies have demonstrated that both alginate and laminarin fibers can be efficiently fermented by the human microbiota [24, 25, 31-35, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The human intestinal microbiota possess several glycosyl hydrolase genes (29), and the human fecal microbiota are known to hydrolyze DON3Glc (7,10,11). It is therefore likely that DON3Glc hydrolysis occurs in the human intestine, but future experiments are required to provide evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, reconstruction of genes for carbohydrate degradation from gut metagenomic data has indicated that Bacteroides uniformis also exhibits an important glycolytic capability (Tasse et al, 2010 ). Strikingly, the fibrolytic potential of B. uniformis was supported by a recent metagenomic study, which indicates that its dietary fiber degrading role is not restricted to the colon, but it extends to distal regions of the small intestine such as ileum (Patrascu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%